Living a calling in precarious employment: an integrative review of consequences on professional and personal lives - Hult Marja; Lappalainen Kirsi; Kangasniemi Mari (Federation of Occupational Health Nurses, 2026)
The working life trend in recent years has been precarious employment. At the same time, people seek callings and more meaningfulness from work. Therefore, the purpose of this integrative review study is to identify, describe, and synthesize studies on precarious employment and having a calling. An integrative review method was used. Data from eight papers were analyzed using the constant comparison method. Precarious employment and having a calling was a sparsely studied area. Precarious employment was related to job insecurity, poor working conditions, and financial burdens. More subjective characteristics were poor career management and development possibilities, limited autonomy, and tensions concerning workers’ identities. However, some workers chose precarity and financial insecurity to be able to fulfill their calling. Having a calling was related to low-paid professions. Precarious employment offers poor job security, career opportunities, working conditions, and low levels of autonomy. These negatively affect workers’ careers, wellbeing and health and make it hard for them to maintain their calling. Employers should pay attention to the quality of working life and better recognize calling as an important resource in work. Occupational health care can support workers having a calling and who are in precarious employment.